Republic of San Marino : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
Over the last half decade, San Marino's economy has managed to weather the implosion of its offshore banking model, the global crisis, and Italy's decision to put San Marino on a tax blacklist. Together, these shocks resulted in a loss of a third of output since 2008, caused banking system NPLs to rise to over 40 percent-with the largest bank requiring 13 percent of GDP in public support-and pushed up net public debt by some 20 percent of GDP (from virtually nil five years ago). Looking forward, the economy is stabilizing, reflecting the inclusion of San Marino in Italy's tax whitelist, but downside risks persist.